2021
DOI: 10.14715/cmb/2021.67.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Astragalin flavonoid inhibits proliferation in human lung carcinoma cells mediated via induction of caspase-dependent intrinsic pathway, ROS production, cell migration and invasion inhibition and targeting JAK/STAT signalling pathway

Abstract: The aim of the current study was to investigate the anti-lung cancer effects of astragalin. Studies were also undertaken to evaluate its effects on apoptosis induction, ROS production, cellular migration and invasion and JAK/STAT3 signalling pathway. MTT assay was used to evaluate cell viability in NSCLC A549 cells after exposure to astragalin molecule. Apoptosis was investigated using AO/EB staining, comet assay and western blotting assay. Fluorescence microscopy was implemented to estimate ROS production. Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Together with apoptosis protease-activating factor 1 (Apaf-1) and autoactivated Caspase 9, cytochrome c can create an apoptosome that will activate Caspase 3 and carry out the apoptotic process [ 70 ]. More importantly, ROS is one of the causes of cell cycle arrest [ 71 ] and one of the multiple cytokines that the JAK/STAT signaling pathway [ 71 74 ] responds to (Fig. 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…Together with apoptosis protease-activating factor 1 (Apaf-1) and autoactivated Caspase 9, cytochrome c can create an apoptosome that will activate Caspase 3 and carry out the apoptotic process [ 70 ]. More importantly, ROS is one of the causes of cell cycle arrest [ 71 ] and one of the multiple cytokines that the JAK/STAT signaling pathway [ 71 74 ] responds to (Fig. 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows a comprehensive summary of these compounds and their distribution within the Morus alba L. tree. Against prostate [20] and ovarian cancer [21], as well as melanoma [21,22] Against colorectal [23], breast [24], gastric [25], and prostate cancer [26], as well as leukemia [27], and glioblastoma [ Against lung [28,29], gastric [30,31], colorectal [32], breast [33], kidney [34], ovarian [35], liver [36], and prostate cancer [37], as well as leukemia [38] and melanoma [39] Against cervical [42], breast [43][44][45], colorectal [46,47], gastric [48], prostate [49][50][51], lung [52][53][54], ovarian [55], liver [56,57], and pancreatic cancer [58], as well as melanoma [59] and renal cell carcinoma [60] Oxyresveratrol Against liver [64], lung [65,66], colorectal…”
Section: Characterization and Source Distribution Of Bioactive Compou...mentioning
confidence: 99%
“…Moreover, Xu et al reported that AG reduced the viability of human lung carcinoma cells and promoting apoptosis by inducing DNA damage, increasing the levels ofaspases-3, caspases-9, Bax, Bak, and Cyt-C, and decreasing Bcl-2, Bcl-xL, as well as XIAP. Besides, AG administration downregulated the expressions of p-JAK2, p-STAT1, and p-STAT3, diminished migration and invasion cell number, and upregulated the levels of ROS, which indicated that interfering with JAK/STAT signaling pathway might be a possible mechanism of AG to treat lung cancer ( Xu et al, 2021 ). In brief, these findings revealed that AG accelerated lung cancer cell death by inhibiting the growth and migration of cancer cell as well as inactivating the MAPK, NF-кB, and JAK/STAT signaling pathways.…”
Section: Pharmacological Effects Of Agmentioning
confidence: 99%